The frequency of kissing as part of sexual activity differs depending on how men meet their male casual sexual partners. (May 2018) - Cornelisse, Vincent J; Priest, David; Fairley, Christopher K; Walker, Sandra; Bradshaw, Catriona S; Phillips, Tiffany; Chow, Eric PF
Previous studies have shown that men who have sex with men (MSM) who use smartphone dating applications (apps) are at higher risk of gonorrhoea, but not HIV. We have hypothesised that kissing may be a risk factor for oropharyngeal gonorrhoea. We measured differences in kissing practices among MSM who use different methods to find male casual sexual partners (CSPs). If MSM who use apps kiss more CSPs, then this may help to explain why these men are at increased risk of gonorrhoea but not HIV. This was a cross-sectional questionnaire-based study of MSM attending Melbourne Sexual Health Centre, Australia, between March and September 2015. We measured differences in kissing practices among MSM who use different methods to find male casual sexual partners (CSPs). The questionnaire included questions about numbers of CSPs, numbers of CSPs kissed, and how men found CSPs. We surveyed 753 MSM with a median age of 29 years (interquartile range 25–36). Six hundred and one men (79.8%) reported using apps to find CSPs in the last three months. Users of apps had a higher number of CSPs than non-users (5.0 vs. 3.2; p < 0.001). Users of apps kissed a higher number (4.6 vs. 2.2; p < 0.001), and a higher proportion (90.4% vs. 71.0%; p < 0.001) of CSPs compared to non-users. We are currently investigating whether kissing is a significant mode of transmission of gonorrhoea, and if this proves correct then this study suggests that users of apps would particularly benefit from health promotion that addresses this mode of transmission.